Auto-antibodies as predictors of autoimmune disease - Bizzaro, Nicola (Henry Stewart Talks, 2007)
Natural history of autoimmune diseases, Predictive value of autoantibodies, Anti-dsDNA antibodies and SLE, Anti-nuclear antibodies and SLE, Anti-Ro/La antibodies and Sjogren's syndrome, Rheumatoid factor and anti-CCP antibodies in rheumatoid arthritis, Anti-mitochondrial antibodies and primary biliary cirrhosis, Autoantibodies in diabetes, Adrenal cortex antibodies and Addison's disease, Ant-thyroid antibodies and hypothyroidism, Anti-tissue transglutaminase antibodies and celiac disease, Autoantibodies and multiple sclerosis, Anti-saccharomyces cerevisiae antibodies and Crohn's disease
Archived at 2018/05/31